2009
DOI: 10.1016/j.intcom.2009.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Human–computer interaction – Whence and whither?

Abstract: a b s t r a c tIn this article, an overview is presented of the growth of work in human-computer interaction (HCI) over the last 40 years. Inevitably much must be omitted, but the referenced papers may fill some of the gaps. Various formative influences and contributing disciplines are noted. Aspects of research and human factors knowledge are prominent, but attention is also given to technology, applied problems, and design for usability. Finally, after summarizing the growth in three age-group partitions, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 62 publications
0
16
0
4
Order By: Relevance
“…In general, using the technology of electronic networks to create an online classroom is a challenge for teaching in the digital age. Ted Nelson suggested that "such an object and system, properly designed and administered, could have great potential for education, increasing the student's range of choice, his sense of freedom, his motivation, and his intellectual grasp" [23]. However, hypertext, and the related concept of hypermedia, is indeed, a key element of teaching instruction in this environment.…”
Section: Nelson's Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, using the technology of electronic networks to create an online classroom is a challenge for teaching in the digital age. Ted Nelson suggested that "such an object and system, properly designed and administered, could have great potential for education, increasing the student's range of choice, his sense of freedom, his motivation, and his intellectual grasp" [23]. However, hypertext, and the related concept of hypermedia, is indeed, a key element of teaching instruction in this environment.…”
Section: Nelson's Publicationsmentioning
confidence: 99%
“…Nelson introduced that hypertext "is a body of written or pictorial material interconnected in such a way that it could not conveniently be presented or reproduced on paper. It may contain summaries, or maps, of its contents and their interrelations" [23]. Nelson interpreted that Hypertext was a text presentation system of "making rapid, arbitrary jumps, where material stored in one place may offer a link, much like a footnote, to material stored in another, in either the same or a different document" [34].…”
Section: Citation Context Analysis Of Citing Articles On Information mentioning
confidence: 99%
“…Shackel's (1997) Human-Computer Interaction -whence and whither [21] (17 pages). A comprehensive attempt to outline a history from a European, ergonomic perspective.…”
Section: The Sample Of Papersmentioning
confidence: 99%
“…As a consequence, the demand for ICT to support human interaction is mounting. The knowledge of Human-Computer Interaction (HCI) has emerged, as a necessary requirement in an effort to develop technology that support human's mental and physical capabilities [1], [2]. Traditional HCI is about designing computer systems that support people so that they can carry out their activities productively and safely [3].…”
Section: Introductionmentioning
confidence: 99%
“…User interfaces is part of the system and/or technologies with which users can see perceptually, understand conceptually and interact with, physically [3]. HCI is the study and practice of usability [2], [8]. To achieve usability, a user-centered design approach is applied [1].…”
Section: Introductionmentioning
confidence: 99%